Hydrodynamic performance testing of artificial textures using a novel pin-on-disc test method - Pusterhofer, Michael; Maier, Michael; Scharf, Raphael; Haumer, Florian; Grün, Florian (Frontiers in Mechanical Engineering, 2025)
In times of global climate change, the reduction in friction in technical applications is of crucial significance. Surface textures are one possibility for reducing friction in lubricated contacts. To provide a deeper understanding of the effects of surface textures on the tribological performance, this study analyzes wedge-shaped, textured lubrication gaps using a novel test rig with an in situ lubrication gap height measurement. Using this experimental pin-on-disc setup, chevron-shaped and cylindrical textures with two different heights (ht = 10 and 50 µm) were tested under full-film lubrication conditions. The pin was tilted in a very precise way to generate a convergent lubrication gap. The test results show the potential for friction reduction using textures. In general, it can be stated that the investigated textures show clearly different behavior compared to the smooth reference specimens. Mostly, a reduction in friction force was measured for the texture specimens, which was accompanied by a reduction in the lubrication gap height. The system still operates in full-film lubrication, but there is a higher risk of entering the mixed-friction regime. In summary, no universal performance trend for single textures can be stated; it needs to be checked for each specific operating point which texture provides the best enhancement.